2018
DOI: 10.1089/zeb.2017.1532
|View full text |Cite
|
Sign up to set email alerts
|

Computer Animation Technology in Behavioral Sciences: A Sequential, Automatic, and High-Throughput Approach to Quantifying Personality in Zebrafish (Danio rerio)

Abstract: An emergent field of animal personality necessitates a method for repeated high-throughput quantification of behavioral traits across contexts. In this study, we have developed an automated video stimulus approach to sequentially present different contexts relevant to five "personality" traits (exploration, boldness, neophobia, aggression, and sociability), successfully quantifying repeatable trait measurements in multiple individuals simultaneously. Although our method is designed to quantify personality trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Repeatability partitions variance into within-individual (residual) and between-individual components. Biologically, the repeatability of a trait indicates the amount of observed variance that is due to individuals sustaining trait differences between each other (Nakagawa and Schielzeth, 2010), but estimates can be inflated by measurement errors and experimental confounds (Dohm, 2002;Niemelä and Dingemanse, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeatability partitions variance into within-individual (residual) and between-individual components. Biologically, the repeatability of a trait indicates the amount of observed variance that is due to individuals sustaining trait differences between each other (Nakagawa and Schielzeth, 2010), but estimates can be inflated by measurement errors and experimental confounds (Dohm, 2002;Niemelä and Dingemanse, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To reduce this knowledge gap, we quantified the repeatability of aversive learning behaviour in zebrafish (Danio rerio), a popular model organism in cognitive science (Gerlai, 2016;Norton and Bally-Cuif, 2010). Zebrafish exhibit a range of distinct behaviours that can be measured in previously established assays (Fangmeier et al, 2018;Meshalkina et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To reduce this knowledge gap, we quantify the repeatability of aversive learning behaviour in zebrafish (Danio rerio), a popular model organism in cognitive science (Gerlai, 2016; Norton & Bally-Cuif, 2010). Zebrafish exhibit a range of distinct behaviours that can be measured in previously established assays (Fangmeier et al, 2018; Meshalkina et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While this is the first robotics-based setup for zebrafish learning, a few previous efforts have explored other automation techniques. For example, Pather and Gerlai (2009) utilized computer-animated images of zebrafish as rewarding stimuli in a shuttle box task, while (Hicks et al, 2006) used real-time video tracking to deliver rewarding or punishing stimuli, in the form of a change in illumination and brief electric shock, Gerlai et al (2009) showed that zebrafish react to computerized images of a predator, and Fangmeier et al (2018) demonstrated the possibility to use automated video stimulus to quantify behavioral traits in zebrafish. Here, we took a significant step forward by combining engineered stimuli with real-time control, affording the possibility of maneuvering them in the entire experimental tank.…”
Section: Discussionmentioning
confidence: 99%